2019
DOI: 10.3390/molecules24101881
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Furfuryl Alcohol into Ethyl Levulinate over Glucose-Derived Carbon-Based Solid Acid in Ethanol

Abstract: In this study, a carbon-based solid acid was created through the sulfonation of carbon obtained from the hydrothermal pretreatment of glucose. Additionally, ethyl levulinate, a viable liquid biofuel, was produced from furfuryl alcohol using the environmentally benign and low-cost catalyst in ethanol. Studies for optimizing the reaction conditions, such as reaction time, temperature, and catalyst loading, were performed. Under the optimal conditions, a maximum ethyl levulinate yield of 67.1% was obtained. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The yield of EL increased with the calcination temperature for either the ZrO 2 ‐T‐1.5 catalysts or the ZrO 2 ‐M‐1.5 catalysts, and the yield of EL reached 96.4% over 500‐M‐1.5 catalyst, whereas it reached 94.5% over 500‐T‐1.5 catalyst. The catalytic activity of the 500‐M‐1.5 catalyst developed in this study was also compared with other typical catalysts developed/used in other studies for the conversion of FA to EL (Table S3, Supporting Information) . The results clearly indicated that the catalyst developed herein showed superior or comparable activities to the reported catalysts.…”
Section: Resultsmentioning
confidence: 54%
“…The yield of EL increased with the calcination temperature for either the ZrO 2 ‐T‐1.5 catalysts or the ZrO 2 ‐M‐1.5 catalysts, and the yield of EL reached 96.4% over 500‐M‐1.5 catalyst, whereas it reached 94.5% over 500‐T‐1.5 catalyst. The catalytic activity of the 500‐M‐1.5 catalyst developed in this study was also compared with other typical catalysts developed/used in other studies for the conversion of FA to EL (Table S3, Supporting Information) . The results clearly indicated that the catalyst developed herein showed superior or comparable activities to the reported catalysts.…”
Section: Resultsmentioning
confidence: 54%
“…It was found that the suitable hydrothermal carbonization conditions were 220 °C and 6 h, which provided high catalytic activity for cellulose hydrolysis and fructose dehydration reactions, and achieved yields of 43.63 ± 1.62 and 20.29 ± 1.09 wt % for glucose and HMF, respectively. Zhao et al also obtained a carbon-based solid acid from the hydrothermal pretreatment of glucose. They used this solid acid to prepare ethyl acetate from furfuryl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies focused on the use of homogeneous catalysts such as strong mineral acids or metal salts. [26] However, the difficult product separation, catalyst toxicity, and reaction container corrosion led to the exploitation of heterogeneous catalysts, including acidic ion exchange resins [27][28][29], zeolites [30][31][32], (sulfated) zirconia-based catalysts [33][34][35], (supported) heteropolyacids [36][37][38][39], activated carbon [40][41][42], functionalized organosilica materials [43][44][45][46][47][48], ionic liquids [49,50], and several sulfonic acid functionalized materials [51][52][53][54]. Some studies were also conducted employing continuous-flow apparatus [32,44] or microwave-assisted procedures [26,42].…”
Section: Introductionmentioning
confidence: 99%